2012
DOI: 10.1111/j.1365-2702.2012.04153.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing and reducing the use of physical restraints in long‐term geriatric care – a Cochrane review

Abstract: Aims and objectives. To evaluate the effectiveness of interventions to prevent and reduce the use of physical restraints in older people requiring long-term nursing care. Background. Physical restraints are commonly used in geriatric long-term care. However, they are associated with adverse outcomes. Therefore, freedom from physical restraints should be the aim of high-quality nursing care. Design. Systematic review of randomised controlled trials. Methods. This review followed the methods of the Cochrane Hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 37 publications
3
39
3
5
Order By: Relevance
“…The quality of reporting in these trials was judged as good for the intervention development and piloting phases. Thus, our findings are contrary to previous analyses of the quality of reporting on complex interventions [12,13,41]. However, the trials included in our sample are more likely to fulfil the CReDECI criteria, since all trials confirmed adherence to the MRC framework.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The quality of reporting in these trials was judged as good for the intervention development and piloting phases. Thus, our findings are contrary to previous analyses of the quality of reporting on complex interventions [12,13,41]. However, the trials included in our sample are more likely to fulfil the CReDECI criteria, since all trials confirmed adherence to the MRC framework.…”
Section: Discussioncontrasting
confidence: 99%
“…While two trials reported on nearly all criteria, six trials offered information only on half of the items or even less. These results confirm the findings from previous studies [9,11,12,42]. Only half of the trials included an evaluation of the implementation process (CReDECI criterion 12).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A previous study reported that educational programs targeting nursing staff might not be effective in reducing the use of physical restraints in geriatric long-term care [28]. However, our results show that the participation in the education program on the prevention of elderly abuse increased by 160.2% through this project.…”
Section: Discussioncontrasting
confidence: 65%
“…In fact, although there is a paucity of literature reporting restraint-associated benefit, there is an abundance of literature reporting complications of restraint use, such as injury and death (Bowers et al, 2012;Gerolamo, 2006;Hatta et al, 2007;Mohr, Petti, & Mohr, 2003;Zun, 2003). In addition, restraint use has been associated with increased length of hospital stay (Mion et al, 1989, Robbins, Boyko, Lane, Cooper, & Jahnigen, 1987, higher mortality (Mion et al, 1989;Robbins et al, 1987;Zun, 2003), increased rates of nosocomial infections (Mion et al, 1989;Robbins et al, 1987), increased incidence of falls (Mion et al, 1989;Möhler, Richter, Köpke, & Meyer, 2012;Tinetti, Liu, & Ginter, 1992), and aggression-coercion cycles for both patients and staff (Goren, Singh, & Best, 1993;Substance Abuse and Mental Health Service Administration, 2011). A recent integrative review of the qualitative literature revealed that patients often experience physical restraint as demeaning and with negative psychological impacts such as retraumatization in those with previous traumatic experiences (Strout, 2010).…”
Section: Introductionmentioning
confidence: 95%